Transcriptome-Wide Analysis of RNA m6A Methylation and Gene Expression Changes Among Two Arabidopsis Ecotypes and Their Reciprocal Hybrids - Xu, Zhihui; Shi, Xiaobo; Bao, Mengmei; Song, Xiaoqian; Zhang, Yuxia; Wang, Haiyan; Xie, Hairong; Mao, Fei; Wang, Shuai; Jin, Hongmei; Dong, Suomeng; Zhang, Feng; et al. (Frontiers in Plant Science, 2021)
The remodeling of transcriptome, epigenome, proteome and metabolome in hybrids plays an important role in heterosis. N(6)-methyladenosine (m6A) methylation is the most abundant post-transcriptional modification in mRNAs, but the pattern of inheritance from parents to hybrids and potential impact on heterosis are largely unknown. We constructed transcriptome-wide mRNA m6A methylation maps of Arabidopsis thaliana Col-0 and Landsberg erecta (Ler) and their reciprocal F1 hybrids. Generally, the transcriptome-wide pattern of m6A methylation tends to be conserved between the accessions. Approximately 74% of the m6A methylation peaks are consistent between the parents and hybrids, indicating that a majority of the m6A methylation is maintained after hybridization. We found a significant association between differential expression and differential m6A modification, as well as non-additive expression and non-additive methylation on the same gene. The overall RNA m6A level between Col-0 and Ler is clearly different but tended to disappear at the allelic sites in the hybrids. Interestingly, many enriched biological functions of genes with differential m6A modification between parents and hybrids are also conserved, including many heterosis-related genes involved in biosynthetic processes of starch. Collectively, our study revealed the overall pattern of inheritance of mRNA m6A modifications from parents to hybrids and a potential new layer of regulatory mechanisms related to heterosis formation.